Mapping the Landscape of Impostor Phenomenon Research in Organizational Behavior: A Bibliometric Study between 2003 and 2022 - Füsun Çınar Altıntaş; Hümeyra Demirbas (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The Impostor Phenomenon is a psychological phenomenon characterized by an individual's inability to internalize their success despite substantial evidence, leading them to feel like a fraud in their status. This phenomenon is increasingly recognized as an important factor in the success and survival of organizations. However, despite its practical and scientific importance, the Impostor Phenomenon has a relatively short history in the field of organizational behavior. Research into the impostor phenomenon in organizational behavior has seen significant growth between 2003 and 2022. This study aims to provide a comprehensive overview of the research status of this topic during this period and to determine the main and sub-themes in which this concept has been examined in academic contexts. The current study focuses on determining which main and sub-themes this concept is examined in academic context. In the study, the articles in the web of science database were examined. The articles were analyzed by performing Bibliometrics analysis with the Vosviewer program. It is aimed to determine and cluster the network relations of the concepts with each other. It has been determined that five basic clusters are word or concept-based representation of imposter phenomenon. These clusters are named as “Organizational Psychology”, "Business Management”, “Sustainable Business”, “"Human Resource Management and Positive Psychology” and "Organizational Change Management."